Comparison of SEER Treatment Data With Medicare Claims. Issue 9 (September 2016) - Noone, Anne-Michelle; Lund, Jennifer L.; Mariotto, Angela; Cronin, Kathleen; McNeel, Timothy; Deapen, Dennis; Warren, Joan L.
Abstract : Background: The population-based Surveillance, Epidemiology, and End Results (SEER) registries collect information on first-course treatment, including surgery, chemotherapy, radiation therapy, and hormone therapy. However, the SEER program does not release data on chemotherapy or hormone therapy due to uncertainties regarding data completeness. Activities are ongoing to investigate the opportunity to supplement SEER treatment data with other data sources. Methods: Using the linked SEER-Medicare data, we examined the validity of the SEER data to identify receipt of chemotherapy and radiation therapy among those aged 65 and older diagnosed from 2000 to 2006 with bladder, female breast, colorectal, lung, ovarian, pancreas, or prostate cancer and hormone therapy among men diagnosed with prostate cancer at age 65 or older. Treatment collected by SEER was compared with treatment as determined by Medicare claims, using Medicare claims as the gold standard. The κ, sensitivity, specificity, positive predictive values, and negative predictive values were calculated for the receipt of each treatment modality. Results: The overall sensitivity of SEER data to identify chemotherapy, radiation, and hormone therapy receipt was moderate (68%, 80%, and 69%, respectively) and varied by cancer site, stage, and patient characteristics. The overall positive predictive value was high (>85%) for all treatment types and cancer sites except chemotherapy for prostate cancer. Conclusions: SEER data should not generally be used for comparisons of treated and untreated individuals or to estimate the proportion of treated individuals in the population. Augmenting SEER data with other data sources will provide the most accurate treatment information. Abstract : Supplemental Digital Content is available in the text.